Exponential Attractors for Parabolic Equations with Dynamic Boundary Conditions - Zhao-hui Fan (Journal of Applied Mathematics)
We study exponential attractors for semilinear parabolic equations with dynamic boundary conditions in bounded domains. First, we give the existence of the exponential attractor in by proving that the corresponding semigroup satisfies the enhanced flattering property. Second, we apply asymptotic a priori estimate and obtain the exponential attractor in . Finally, we show the exponential attractor in .